Present And Future Indonesian Maritime Leadership - Yuslita Rinika; Abdul Rivai Ras; Bayu Asih Yulianto; Herlina Juni Risma Saragih; Pujo Widodo (CV. AFDIFAL MAJU BERKAH, 2023)
After decades of being behind the back, the words sea and maritime have begun to be echoed again after President Joko Widodo's speech at the 9th East Asia Summit, in Nay Pyi Taw, Myanmar, 13 November 2014 which wished to make Indonesia a World Maritime Axis (PMD). In order to make PMD successful, the President and Cabinet Ministers lowered various policies and government action programs starting from the national level down to a lower and more realistic level. Like the sinking of ships carrying out IUU fishing carried out by the Ministry of Maritime Affairs and Fisheries. PMD policy implementation invites a reactive attitude from countries inside and outside the Southeast Asian region. and there are big countries outside the region that seem not to support or oppose it. In the second period maritime issues are no longer visible, now it has been 8 years since the leadership of President Joko Widodo continues. The vision of making Indonesia the world's maritime axis seems to be swallowed up by time. The results of the execution of programs such as the construction of international standard ports and maritime highways are not yet clear. Indonesia still has a lot to improve itself. Even though development activities are currently focused on post-covid economic recovery and all anticipation of a new wave. The World Maritime Axis is no longer a major issue. However, at least the PMD program triggers the community and other elements of the nation to develop a sense of love and ownership of the sea. The results of the execution of programs such as the construction of international standard ports and maritime highways are not yet clear. Indonesia still has a lot to improve itself. Even though development activities are currently focused on post-covid economic recovery and all anticipation of a new wave. The World Maritime Axis is no longer a major issue. However, at least the PMD program triggers the community and other elements of the nation to develop a sense of love and ownership of the sea. The results of the execution of programs such as the construction of international standard ports and maritime highways are not yet clear. Indonesia still has a lot to improve itself. Even though development activities are currently focused on post-covid economic recovery and all anticipation of a new wave. The World Maritime Axis is no longer a major issue. However, at least the PMD program triggers the community and other elements of the nation to develop a sense of love and ownership of the sea.